Aktualisasi Permainan Edukatif Digital Pada Anak Usia di Igtk Tasikmadu Karangnyar - Nasrudin Chandra Pramana; Mukti Widayati; Veronika Unun Pratiwi (Universitas Sahid Surakarta, 2025)
The urgency of this service lies in the development of digital technology that has changed children's learning patterns, including in early childhood. Many educators have not fully utilized technology in the learning process. This Community Service is focused on the role of teachers and teachers' understanding in the application and use of digital media in learning in kindergartens in the IGTKI Tasikmasdu Karanganyar environment. The method used is in the form of qualitative descriptive with systematic stages starting from socialization to several kindergarten schools, training on the actualization of digital educational games, the application of technology in the use of digital educational games, mentoring and evaluation, ending with the sustainability of the ABC Kids digital educational game actualization training program at IGTKI Tasikmadu Karanganyar. The implementation of Community Service consists of several stages, namely observation, socialization; Training; and evaluation. Data was obtained by observation techniques and questionnaire distribution. Strengthening literacy skills at an early age through an interesting and innovative approach based on the actualization of ABC Kids digital educational games is very important to prepare children to face global challenges through improving reading and numeracy skills. This training aims to provide understanding and skills to educators at IGTKI Tasikmadu Karangnyar regarding the use of ABC Kids digital educational games as a fun and effective learning medium in improving literacy culture in early childhood. The results of the service showed a positive impact on learning for both teachers and children with the following survey results 82% of teachers understood, 90% of teachers were skilled in operationalizing, 87 teachers had implemented, and 88% of the results of the presentation met the KKM.